Lovers dan Haters Ujian Berat Jurnalisme (Studi Postmodern) - Sisca T. Gurning (VISIONER : Jurnal Komunikasi, Bisnis dan Konten Kreatif, 2018)
The development of information technology has changed the map of journalism that initially the task of reporting information only owned by mainstream media owners. Nowadays it is very easy for internet citizens (netizens) to have smartphones (smartphones) so that everyone can have a medium to spread information into citizen journalism. Spreading the information does not need to wait for news from the mainstream media, every second or minute we easily get information through the existing smartphones in our hands. Information in this postmodern era, also because of the dissatisfaction and distrust of the public to the conventional media, because more news is constructed by the owners of media for economic and political interests. This study aims to open the issue of how journalists and owners of conventional media in news editorial policy. Internet citizens have an impact on the making of news viewed from the perspective of postmedern theory on journalism and culture study media which has given birth to consumerist society, based on lovers case and haters at the news of former governor of DKI Jakarta, Basuki Tjahaja Purnama. The results show a considerable influence how the press workers in constructing their news can not be critical. This era is an era that does not believe in the big narrative and replaced with small narratives with the death of rationality so that now journalism has a hard test